The response of growth two clone of tea (Camellia sinensis) with coconut water application after centering - Ai Yanti Rismayanti; Santi Rosniawaty; Sumadi Sumadi (Research Institute for Tea and Cinchona, 2017)
Vegetative stage is an essential element for plants that shoot harvested. At that stage, the growth regulator application can directly increase the production quantively accelerate the potential formation and growth of roots and shoots. Coconut water is one of aÂ natural sources of growth hormone that has a potency to increase the early growth of the tea plant. This experiment aimed to find out the response of tea plant growth on the lowlands after centering with coconut water application. This experiment was conducted in experimental garden of Faculty of Agriculture Unpad, Jatinangor, Sumedang at an altitude of 750 m above sea level and Inceptisol terrestrial soil. The experiment began in February 2016 until June 2016 using Split Plot Design, consisting of two factors and three replications. The main plot is a type of clone (K) which consists of two levels, namely: k1 = GMB 7, k2 = GMB 11. Sub plot is a coconut water concentration (A) consisting of five levels: a0 = coconut water application (control), a1 = coconut water concentration 25%, a2 = coconut water concentration 50%, a3 = coconut water 75% concentration, a4 = coconut water 100% concentration. The experimental results showed that coconut water had a significant effect on all treatments. The interaction of plant height variable at 14 WAC - 16 WAC (Week After Centering), canopy width at 12 WAC - 16 WAC and stem diameter at 14 WAC - 16 WAC and no significant effect on plant height at 2 WAC - 12 WAC, canopy width at 2 WAC - 10 WAC, and stem diameter at 2 WAC - 12 WAC, at 2 WAC - 12 WAC. In general, GMB 11 clone tea plant that applied 75% coconut water performed the best growth response on tea growth in the lowlands after centering.